VD_FINDINFO Arrêt / 2020 / 879 vom 17. November 2020 - VD Tribunal cantonal (2020)
AVS, COTISATION AVS/AI/APG, PRESTATION D'ASSURANCE{AVS/AI/PC}, CONJOINT, DOMICILE À L'ÉTRANGER | 5 al. 3 Cst., 8 al. 1 Cst., 9 Cst., 1a al. 1 LAVS, 1a al. 1 let. b LAVS, 29 LAVS, 29bis al. 1 LAVS, 29bis al. 2 LAVS, 29ter LAVS